Observation Hive Marking Apparatus (OHMA): an inexpensive method for mass-marking honey bees in observation hives. - Bonoan, Rachael E.; Philip T. Starks (Tufts Archival Research Center, 2017)
This paper outlines our modified method of mass-marking honey bees in observation hives. Our method is inexpensive and widely applicable to research on honey bees, and other pollinators.